Mobilizing Private Finance for Development in Latin America and the Caribbean - Abousleiman, Issam A.; Thompson Araujo, Jorge (World Bank, Washington, DC, 2018)
The Latin America and the Caribbean Region (LAC) has the largest stock of active PPP investments and the largest pipeline of infrastructure projects by volume globally, reflecting the central role of the private sector in the regional development agenda. Looking ahead, the region is making efforts to close the estimated US$180 billion per year investment gap with further private sector resources by: (i) improving the enabling environment for private investments to take place; and (ii) developing a robust pipeline of bankable projects. The WBG is well-placed to assist the region with financial support and knowledge services, as illustrated by the examples selected for part three of this report.